Effects of light quality and photoperiod on growth and photosynthetic pigment content of a Rhodophyta, Gloiopeltis furcata - Zhang, Wenwen; Zhu, Changbo; Chen, Suwen (Fisheries science, 2020)
The objective of the present study was to determine the optimal incubation conditions for Gloiopeltis furcata culture. Three experiments, each lasting 30 days, were conducted to study the effects of photoperiod (6:18, 8:16, 12:12, 14:10, and 16:8 h light/dark), different wavelengths of LED light (blue, green, yellow, red, and white), and solar radiation filtered through different plastic films (blue, green, yellow, red, and white) on the growth and photosynthetic pigment content of G. furcata . The results of these experiments demonstrated that the growth rate of G. furcata was significantly higher under 14:10 and 16:8 light/dark than under 6:18 and 8:16 light/dark, while the pigment content of G. furcata was significant higher under 6:18 and 8:16 than under 14:10 and 16:8 light/dark. The growth rate of G. furcata was the lowest when the algae were exposed to blue LED and the highest under yellow LED illumination, while the phycobiliprotein content was the highest under blue LED and the lowest under yellow LED. Solar radiation filtered through different plastic films had no significant effect on the growth rate of G. furcata , but affected its pigment content. The results indicate that a photoperiod of 12 h or more of light and yellow LED are the optimal parameters for culturing of G. furcata thalli on land.